2022
DOI: 10.3390/jcm11175064
|View full text |Cite
|
Sign up to set email alerts
|

Primary Staging of Prostate Cancer Patients with [18F]PSMA-1007 PET/CT Compared with [68Ga]Ga-PSMA-11 PET/CT

Abstract: Background: Hybrid imaging with prostate-specific membrane antigen (PSMA) is gaining importance as an increasingly meaningful tool for prostate cancer (PC) diagnostics and as a guide for therapy decisions. This study aims to investigate and compare the performance of [18F]PSMA-1007 (18F-PSMA) and [68Ga]Ga-PSMA-11 positron emission tomography/computed tomography (68Ga-PSMA) in the initial staging of PC patients. Methods: The data of 88 biopsy-proven patients were retrospectively evaluated. PSMA-avid lesions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Staging PSMA PET/CT of high-risk PCa patients detects lymph node metastases for almost a third of the patients and bone metastases for a sixth of the patients, as reported in a recent review ( 25 ). The estimates fit with recent literature ( 6 - 14 ). So staging PSMA shows metastatic PCa for half of the high-risk patients.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…Staging PSMA PET/CT of high-risk PCa patients detects lymph node metastases for almost a third of the patients and bone metastases for a sixth of the patients, as reported in a recent review ( 25 ). The estimates fit with recent literature ( 6 - 14 ). So staging PSMA shows metastatic PCa for half of the high-risk patients.…”
supporting
confidence: 71%
“…Other studies reported that staging PSMA PET/CT gave a similar or slightly higher frequency of patients with miN1/miM1 ( 6 - 14 ). Zheng et al showed that staging PSMA PET/CT gave pathological upgrading for 27% of the patients and a downgrading for 23% of the patients ( 6 ).…”
mentioning
confidence: 81%
“…FIGURE 2. For staging, 18 F-PSMA-1007 PET/CT scan was performed [1][2][3]. Anterior (A) and lateral (B) MIP PET showed an irregular area (arrows) of heterogeneous activity in the prostate region.…”
mentioning
confidence: 99%
“…For staging, 18 F-PSMA-1007 PET/CT scan was performed. [1][2][3] Anterior (A) and lateral (B) MIP PET showed an irregular area (arrows) of heterogeneous activity in the prostate region. Transverse CT at the levels of the mid (C) and basal (D) prostate, corresponding PET (E and F) and fused (G and H) images showed heterogeneous activity (straight arrows) of the prostate and intense heterogeneous activity (curved arrow) with SUV max of 11.9 of the mass of the left seminal vesicle.…”
mentioning
confidence: 99%
“…FIGURE 2. For staging, 18 F-prostate-specific membrane antigen (PSMA) 1007 PET/CT scan was performed [1][2][3]. Maximum intensity projection PET (A) showed multifocal activity in the prostatic (straight arrow) and right pelvic regions (arrowheads) and physiologic urinary activity within the bladder (curved arrow).…”
mentioning
confidence: 99%